Persepsi Tentang Pengaruh Lingkungan Sosial, Lokasi, Pengetahuan dan Religiusitas Masyarakat Terhadap Keputusan dalam Penggunaan Produk Penghimpunan Dana di Bank Syariah Indonesia Cabang Trenggalek - Helfmia Ristyanty Karta Eka Praja; Syafrudin Arif Marah Manunggal (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Currently, a sharia-based economy has begun to gain ground, especially the banking sector by implementing the principles of openness and profit sharing which are felt to be able to provide justice for its customers. Society is a segmentation that has potential for saving activities. The purpose of this research is to find out whether the social environment, location, knowledge and religiousness of the community influence decisions regarding the use of fund collection products at Bank Syariah Indonesia, Trenggalek Branch. This research is quantitative research. The population in this study were residents of Gador Village, Durenan District, Trenggalek Regency. The sample consisted of 209 residents. The sampling technique is purposive random sampling technique. The data collection method is a questionnaire distributed to respondents from October-December 2023. This research using multiple linear regression data analysis techniques. The results of the t test show that partially the Social Environment has no influence on Product Use Decisions, Location has an influence on Product Use Decisions, Knowledge has an influence on Product Use Decisions, and Religiosity has an influence on Product Use Decisions. Meanwhile, the results of the F test simultaneously, Social Environment, Location, Knowledge and Religiosity have an influence on Product Use Decisions